Viscous microneedle patch for tracheal fistula plugging and preparation method thereof
By using a double-layer structure microneedle patch with expandable mechanical fixation effect driven by mussel adhesion protein and microneedle on the tracheal fistula, the problem of difficulty in healing the tracheal fistula is solved, and sealing and tissue regeneration of the tracheal fistula is achieved. It reduces the inflammatory response and provides better clinical application prospects.
Patent Information
- Application Number
- CN202411527812.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2024-12-27
AI Technical Summary
Tracheal fistula is difficult to heal on its own, and the existing treatment methods are not effective, mainly due to the severe inflammatory environment and oxidative stress reaction at the fistula, which affects the regeneration of defective tissue.
Using microneedle patches with adhesion bilayer structures, using the wet adhesion properties of mussel adhesion protein and the expandable mechanical fixation effect of microneedles, a sealant for tracheal fistula is designed by carrying growth-promoting factors. and antioxidants, the bilayer structure regulates the fistula microenvironment and reduces inflammatory response and oxidative stress.
The tracheal fistula sealing under humid and dynamic conditions is achieved, which promotes tracheal tissue regeneration, reduces inflammatory response, and improves the effect of tracheal fistula healing and defect repair. It is simple to operate and low cost, avoiding the tension problem of traditional sutures.
Smart Images

Figure CN119185171A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of bioengineering, and in particular to an adhesive microneedle patch for blocking tracheal fistula and a preparation method thereof. Background Art
[0002] Tracheal fistula is caused by damage to the airway wall due to cancer, mechanical ventilation injury, stent-related trauma, or contact with corrosive objects. When the fistula is small, there is a chance that it will close on its own, but larger fistulas are difficult to heal on their own, and in severe cases, it leads to poor quality of life or even death for patients. Therefore, blocking fistula is one of the thorny clinical problems, and it is also an important measure that can temporarily close the fistula, restore the continuity of the patient's respiratory function, prevent the contents from spilling out, and avoid the contents from corroding surrounding tissues and causing fatal complications such as severe infection.
[0003] At present, the main clinical treatment methods for tracheal fistula are surgery, intervention and conservative drug therapy. Although these conventional therapies have certain effects on the treatment of tracheal fistula, the efficacy is still poor, which is mainly due to the particularity of the pathological microenvironment of the fistula. First of all, the tracheal structure at the fistula is severely damaged, the cartilage softens and collapses, the epithelial layer is completely destroyed, and the anti-infection barrier is lost. Therefore, in addition to the structural defects at the tracheal fistula, it is also in a serious inflammatory environment, which further leads to excessive oxidative stress response at the wound, and ultimately affects the regeneration of defective tissue, resulting in the tracheal fistula not healing for a long time. Therefore, designing a fistula plugging tool that can actively regulate the regeneration microenvironment of the fistula and reduce the level of inflammatory response and oxidative stress at the fistula site is of great significance for the healing of tracheal fistula and the repair of defective tissue.
[0004] The microneedle patch is composed of tiny needles with a length of 1 mm. Compared with the conventional injection needle system, it can deliver therapeutic drugs to the target site more effectively through microchannels and reduce trauma and pain. Currently, microneedle patches have gradually been used for the delivery of macromolecules. Summary of the invention
[0005] The purpose of the present invention is to provide an adhesive double-layer microneedle patch for tracheal fistula occlusion and a preparation method thereof, by utilizing the inherent wet adhesion properties of bioengineered mussel adhesive protein and the expandable mechanical fixation effect driven by microneedles, so that the microneedle patch can become a new type of tracheal fistula sealant under wet and dynamic conditions.
[0006] In a first aspect of the present invention, there is provided a method for preparing an adhesive microneedle patch for tracheal fistula occlusion, comprising the following steps:
[0007] (A) Preparation of microneedle patch master mold:
[0008] The master mold of the microneedle patch was prepared by grayscale photolithography; a 1 mm thick anionic photoresist was coated on a glass wafer and baked for 12 hours, and then cast with polydimethylsiloxane (PDMS) to obtain the master mold; the master mold consisted of 10×10 conical microneedles, with a needle tip spacing of 750 μm, a microneedle base diameter of 250 μm, a height of 750 μm, and a needle tip radius of <15 μm; a cubic patch mold (1 cm×1 cm×0.5 cm) was set in the middle of the master mold ( Figure 1 ).
[0009] (B) Preparation of a double-layer microneedle patch based on mussel adhesive protein:
[0010] Preparation of microneedle tips: Load the first layer of 35 μL of pre-hydrogel solution, including 70% (wt. vol. -1 ) silk protein solution, 10 μg of PEGylated manganese-doped hollow mesoporous silica nanoparticles loaded with growth factors (growth factors include fibroblast growth factor, insulin-like growth factor, and vascular endothelial growth factor, and the concentration of vascular endothelial growth factor and fibroblast growth factor is 10 ng mL -1 , IGF concentration was 20 ng mL -1 )、1mM Ru(II)bpy3 2+ and 30 mM sodium persulfate dissolved in PBS; loaded into the microneedle patch master mold, and dried in a vacuum system (-85 kPa) for 15 minutes;
[0011] Preparation of microneedle base: Load the second layer of hydrogel pre-solution, including 35% (wt. vol. -1 ) mussel adhesive protein, 15% (wt.vol -1 ) hyaluronic acid, 1mM Ru(II)bpy3 2+ and 30 mM sodium persulfate dissolved in PBS; it should be pointed out that the second layer of hydrogel (outer layer) at the cubic patch is a ROS-responsive polyvinyl alcohol-phenylboronic acid acrylate-quercetin hydrogel (20 μM) composited in the above-mentioned hydrogel pre-solution and dried under -85 kPa vacuum for 12 hours; then the completely dried microneedle patch was gently peeled off from the mold; throughout the production process, fluorescent illumination was used to ensure that blue light triggered the cross-linking between the mussel adhesion protein and the silk protein tyrosine residues.
[0012] Furthermore, the method for preparing the polyethylene glycol manganese doped hollow mesoporous silica nanoparticles described in step B comprises the following steps:
[0013] 1. Synthesis of mesoporous silica nanoparticles: Hexadecyltrimethylammonium chloride (2 g) and triethanolamine (0.02 g) were diluted with 20 mL of water and magnetically stirred at 80 ° C for 20 min; 1.5 mL of ethyl silicate was added dropwise to the solution, and the mixture was stirred at 80 ° C for another 4 h; the product was collected by centrifugation (18000 r / min, 15 min) and washed three times with ethanol and water to remove residual precursors and reactants; the surfactant impurities were removed by stirring in a methanol solution of sodium chloride (8 mg / mL, stirring for 12 h) for 3 rounds;
[0014] 2. Synthesis of manganese-doped hollow mesoporous silica nanoparticles: The synthesized mesoporous silica nanoparticles were dispersed in 10 mL of water; a mixed solution (10 mL) of MnSO4-H2O (8 mg / mL, 80 mg) and disodium maleate (10 mg / mL, 100 mg) was added dropwise to the aqueous solution of mesoporous silica nanoparticles under stirring; the mixture was treated under hydrothermal conditions at 180°C for 12 h; the product was collected by centrifugation and washed several times with ethanol and water to remove residual reactants;
[0015] 3. PEGylation of manganese-doped hollow mesoporous silica nanoparticles: Manganese-doped hollow mesoporous silica nanoparticles (10 mg) were dispersed into M-SLN-2000 ethanol solution (100 mL, 0.5 mg / mL, 50 mg PEG + 100 mL ethanol) under magnetic stirring at 60 ° C; after reacting for 24 hours, the PEGylated manganese-doped hollow mesoporous silica nanoparticles were collected by centrifugation; the product was rinsed with ethanol and deionized water several times to remove residual M-SLN-2000.
[0016] Furthermore, the preparation method of the ROS-responsive polyvinyl alcohol-phenylboronic acid acrylate-quercetin-loaded hydrogel described in step B comprises the following steps:
[0017] 1. Synthesis of phenylboronic acid acrylate: a) Tetramethylpropylenediamine (0.1 g, 0.75 mmol) and 4-(bromomethyl)phenylboronic acid (0.5 g, 2.3 mmol) were dissolved in dimethylformamide (10 ml) and mixed together; b) After stirring at 60° C. overnight (24 h), the mixture was poured into tetrahydrofuran (100 ml), filtered and washed 3 times with tetrahydrofuran (3×20 ml); c) After vacuum drying overnight, pure phenylboronic acid acrylate was obtained;
[0018] 2. Formation of polyvinyl alcohol-phenylboronic acid acrylate-quercetin hydrogel: a) polyvinyl alcohol (72 kDa, 98% hydrolyzed, 5 g) and deionized water (100 ml) were mixed together and stirred at 90°C to obtain a clear solution; b) quercetin (quercetin was dissolved in DMSO at a concentration of 20 μM) was added to the clear solution; c) phenylboronic acid acrylate (2 mL of a 5% mass fraction aqueous solution) and polyvinyl alcohol (2 mL of a 5% mass fraction aqueous solution) were mixed together and a hydrogel was immediately formed.
[0019] In the preparation method of the microneedle patch of the present invention, 1) when the master mold of the microneedle patch is prepared, the size needs to match the size of the tracheal fistula, and the microneedle spacing and length need to be moderate to ensure the piercing effect; 2) the mussel adhesive protein of the inner layer (microneedle bottom) has wet adhesion characteristics and an expandable mechanical fixation effect, thereby assisting the cubic patch to be fixed at the fistula defect. The protein concentration ratio of the present invention is obtained by exploring the changes in material viscosity and toughness brought about by the concentration and ratio of different polymers. 3) In the synthesis of polyethylene glycol manganese doped hollow mesoporous silica nanoparticles in the outer layer (microneedle shell), it plays a role because it carries growth factors and slowly releases them. During the synthesis process, the medium needs to be fully dissolved, the time and speed of magnetic stirring need to be controlled, and the stirring temperature also needs to be accurately controlled to avoid unnecessary chemical reactions. 4) In the preparation process of the ROS-responsive polyvinyl alcohol-phenylboronic acid acrylate hydrogel in the outer layer (fistula-blocking cubic shell), the mass ratio of the three components (see above) in phenylboronic acid acrylate is explored to obtain the optimal ROS scavenging ability.
[0020] In a second aspect of the present invention, there is provided an adhesive microneedle patch for tracheal fistula occlusion, which is prepared by the preparation method as described above.
[0021] The third aspect of the present invention provides a use of the adhesive microneedle patch as described above in the preparation of a product for treating tracheal fistula.
[0022] Furthermore, the product for treating tracheal fistula is a product for blocking tracheal fistula.
[0023] Furthermore, the product for treating tracheal fistula is a product for repairing tracheal defective tissue.
[0024] When the present invention is used, it targets the destruction of the airway wall caused by clinical cancer, mechanical ventilation injury, stent-related trauma or contact with corrosive objects. During use, the patient's tracheal fistula is first exposed, and the fistula is cleaned (including blood removal, pus removal, etc.), and then the doctor adheres the prepared microneedle patch to the fistula, and squeezes it slightly to adhere it to the defect. By utilizing the inherent wet adhesion properties of bioengineered mussel adhesion protein and the expandable mechanical fixation effect driven by microneedles, the microneedle patch can be tightly adhered to the tracheal fistula without being fixed again with sutures, thereby playing a blocking role. And then it remains in the patient's body to play a regeneration-promoting effect and gradually degrades after 4 weeks.
[0025] The advantages of the present invention are:
[0026] The present invention constructs an adhesive double-layer microneedle patch for tracheal fistula occlusion. By utilizing the inherent wet adhesion properties of bioengineered mussel adhesion proteins and the expandable mechanical fixation effect driven by microneedles, the microneedle patch can become a new type of tracheal fistula sealant under humid and dynamic conditions. The main advantages of the present invention are as follows: 1) low production cost, simple raw materials and high biosafety; 2) simple clinical operation. Compared with traditional direct surgical sutures, the patch can avoid anastomotic tension and play a better adhesion and occlusion role; 3) traditional repair methods mainly rely on the repair function of the patient's own tissue, but this patch can play an anti-inflammatory and regenerative role in the future through the design of a double-layer structure, and is degradable, helping patients with tracheal fistula wounds to recover faster. Therefore, this microneedle patch has great prospects for clinical application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 : Microneedle patch design scheme; A: Top view of microneedle patch; B: Double-layer microneedle design concept; C: Central cubic patch design concept.
[0028] Figure 2 : Anti-active oxygen properties of hydrogel system.
[0029] Figure 3 : Gel strength test.
[0030] Figure 4 : Swelling properties of mussel protein layer.
[0031] Figure 5 : Nanoparticle morphology.
[0032] Figure 6 :Nanoparticles promote cartilage regeneration. DETAILED DESCRIPTION
[0033] The specific implementation methods provided by the present invention are described in detail below in conjunction with examples.
[0034] Example 1: Preparation method of the adhesive microneedle patch for tracheal fistula occlusion of the present invention
[0035] The present invention provides an adhesive double-layer microneedle patch for treating tracheal fistula and promoting tracheal tissue regeneration. A ROS-responsive double-layer patch is used to block the fistula opening. In order to further enhance the adhesion effect of the patch at the fistula opening, an adhesive double-layer microneedle is used for fixation and drug loading to promote enhanced tracheal tissue regeneration. The preparation method of the microneedle patch comprises the following steps:
[0036] The master mold of the microneedle patch was prepared by grayscale photolithography. A 1 mm thick anionic photoresist was coated on a glass wafer and baked for 12 hours. The master was then cast with polydimethylsiloxane to obtain the prepared master. The master mold consisted of 10×10 conical microneedles with a tip spacing of 750 μm, a base diameter of 250 μm, a height of 750 μm, and a tip radius of <15 μm. A cubic patch mold (1 cm×1 cm×0.5 cm) was designed in the middle of the master mold ( Figure 1 ).
[0037] Next, a double-layer microneedle patch based on mussel adhesive protein was prepared. To prepare the tip of the microneedle (i.e., the first outer layer), a first layer of 35 μL of pre-hydrogel solution was loaded, which included 70% (wt. vol. -1 ) silk protein solution, 10 μg polyethylene glycol manganese doped hollow mesoporous silica nanoparticles (carrying growth factors including fibroblast growth factor, insulin-like growth factor, vascular endothelial growth factor, vascular endothelial growth factor, fibroblast growth factor concentration of 10 ng mL -1 , IGF concentration was 20 ng mL -1 )、1mM Ru(II)bpy3 2+ and 30 mM sodium persulfate dissolved in PBS. Placed in a PDMS mold and dried for 15 minutes in a vacuum system (-85 kPa). Then, in order to prepare the microneedle base (i.e., the base inside the first outer layer), a second layer of pre-hydrogel solution was loaded, including 35% (wt. vol. -1 )Mussel adhesive protein, 15% (wt.vol -1 ) hyaluronic acid, 1mM Ru(II)bpy3 2+ and 30mM sodium persulfate dissolved in PBS. Loaded into the microneedle patch master mold and dried in a vacuum system (-85kPa) for 15 minutes. For the fistula, the second layer of hydrogel in the cubic patch was composited with ROS-responsive polyvinyl alcohol-phenylboronic acid acrylate-quercetin hydrogel and dried under -85kPa vacuum for 12 hours. The completely dried microneedle patch was then gently peeled off from the mold. Throughout the production process, fluorescent illumination was used to ensure that blue light triggered the cross-linking between the tyrosine residues of mussel adhesive protein and silk fibroin.
[0038] Among them, the synthesis of manganese-doped hollow mesoporous silica nanoparticles: 1. Synthesis of mesoporous silica nanoparticles: Hexadecyltrimethylammonium chloride (2 g) and triethanolamine (0.02 g) were diluted with 20 mL of water in sequence and magnetically stirred at 80 ° C for 20 min; 1.5 mL of ethyl silicate was added dropwise to the solution, and the mixture was stirred at 80 ° C for another 4 h; the product was collected by centrifugation (18000 r / min, 15 min), and washed three times with ethanol and water to remove residual precursors and reactants; stirred in a methanol solution of sodium chloride (8 mg / mL, stirring for 12 h) for 3 rounds to remove surfactant impurities. 2. Synthesis of manganese-doped hollow mesoporous silica nanoparticles: The synthesized mesoporous silica nanoparticles were dispersed in 10 mL of water; a mixed solution (10 mL) of MnSO4-H2O (8 mg / mL, 80 mg) and disodium maleate (10 mg / mL, 100 mg) was added dropwise to the aqueous solution of mesoporous silica nanoparticles under stirring; the mixture was treated under hydrothermal conditions at 180°C for 12 h; the product was collected by centrifugation and washed several times with ethanol and water to remove residual reactants. 3. Pegylation of Mn-HMSN: Manganese-doped hollow mesoporous silica nanoparticles (10 mg) were dispersed into M-SLN-2000 ethanol solution (100 mL, 0.5 mg / mL, 50 mg PEG + 100 mL ethanol) under magnetic stirring at 60 °C; after reacting for 24 hours, the pegylated manganese-doped hollow mesoporous silica nanoparticles were collected by centrifugation; the product was rinsed with ethanol and deionized water several times to remove residual M-SLN-2000.
[0039] Synthesis of ROS-responsive polyvinyl alcohol-phenylboronic acid acrylate-loaded quercetin hydrogel: 1. Synthesis of phenylboronic acid acrylate: a) Tetramethylpropylenediamine (0.1 g, 0.75 mmol) and 4-(bromomethyl)phenylboronic acid (0.5 g, 2.3 mmol) were dissolved in dimethylformamide (10 ml) and mixed together; b) After stirring at 60 °C overnight (24 h), the mixture was poured into tetrahydrofuran (100 ml), filtered and washed 3 times with tetrahydrofuran (3×20 ml); c) After vacuum drying overnight, the obtained Pure phenylboronic acid acrylate; 2. Formation of polyvinyl alcohol-phenylboronic acid acrylate-quercetin hydrogel: a) polyvinyl alcohol (72 kDa, 98% hydrolyzed, 5 g) and deionized water (100 ml) were mixed together and stirred at 90°C to obtain a clear solution; b) quercetin was added to the clear solution (quercetin was dissolved in DMSO at a concentration of 20 μM); c) phenylboronic acid acrylate (2 mL of 5% mass fraction aqueous solution) and polyvinyl alcohol (2 mL of 5% mass fraction aqueous solution) were mixed together and a hydrogel was formed immediately.
[0040] Through the above steps, a microneedle patch with a composite double-layer structure was constructed.
[0041] Embodiment 2:
[0042] The rabbit model was used to verify the efficacy of microneedles: fistula (1×1 cm defect), firstly, a cubic patch was used to quickly block the fistula, and the ROS-responsive gel was used to balance the oxidative stress environment at the wound. Then, the adhesion microneedle was used to promote fixation, and the tracheal defect tissue was further repaired by the release of nanoparticles.
[0043] The double-layer microneedle patch has the following main functions:
[0044] 1) Use the adaptive cubic patch to achieve oxidative stress environment regulation: The role of the outer layer (shell): Because it is mixed with active oxygen responsive polyvinyl alcohol-phenylboronic acid acrylate-quercetin hydrogel, the hydrogel can release the drug quercetin through ROS sensing in the environment of oxidative stress activation around the fistula. The DPPH free radical scavenging experiment was used to verify that the patch has an antioxidant effect. Specifically, first, a certain concentration of DPPH ethanol solution was prepared as the free radical source of the experiment, and then the hydrogel solution and DPPH solution were measured and mixed to ensure the uniformity of the reaction; the mixed solution was incubated for a certain period of time under light-proof conditions to allow the antioxidant to fully react with the DPPH free radical; the absorbance of the mixed solution was measured at a wavelength of 517nm using a spectrophotometer; the absorbance of the mixture was compared with the absorbance of the DPPH solution, and the DPPH scavenging ability of the sample was calculated ( Figure 2 ).
[0045] The gel friction adhesion test demonstrated that the mussel adhesive protein in the inner layer (bottom) has inherent wet adhesion properties ( Figure 3 ). Simply put, the hydrogel adhesive is placed between two harder substrate specimens for lap shear testing (i.e., mutual displacement friction), and the relationship between adhesion force and displacement is obtained by a universal testing machine, and finally the adhesion strength of the hydrogel is obtained.
[0046] Heavy load test proves the mechanical tensile strength of microneedle patch ( Figure 4 ), that is, hang weights of different masses under the hydrogel and record the weight until it breaks. Finally, combined with the swelling experiment, it is confirmed that mussel protein has an expandable mechanical fixation effect. The hydrogel is placed in PBS buffer, taken out every two hours, the mass is measured, and the current mass is subtracted from the initial mass and then divided by the initial mass to obtain the swelling rate of the hydrogel. Therefore, it can better assist the cubic patch to be fixed at the fistula defect.
[0047] 2) Use microneedle patches to promote tracheal tissue regeneration. The outer layer (shell) of the microneedle patch is mixed with factor-carrying nanoparticles (about 20-30nm in diameter) ( Figure 5), and the cartilage col2 gene detection verified that the nanoparticles have the function of promoting cartilage regeneration after sustained release ( Figure 6 ). Genetic testing is done by means of PCR, which simply includes three stages. Denaturation stage: The hydrogen bonds of the double-stranded DNA are broken at high temperature to form single-stranded DNA.
[0048] Annealing stage: lower the temperature to allow the COL2 gene primer to bind to the DNA template to form a local double strand. The primer is a specific sequence designed artificially, which binds to the complementary sequence of the template DNA to prepare for the next extension reaction. Extension stage: under the action of Taq enzyme, dNTP is used as raw material to extend from the 3′ end → 5′ end of the primer to synthesize a DNA chain complementary to the template. This step is usually performed at 70℃-75℃ to ensure that the DNA polymerase efficiently synthesizes new DNA, realizes the exponential amplification of specific DNA fragments, and finally detects the COL2 gene level.
[0049] The preferred embodiments of the present invention have been specifically described above, but the present invention is not limited to the embodiments. Those skilled in the art may make various equivalent modifications or substitutions without violating the spirit of the present invention. These equivalent modifications or substitutions are all included in the scope defined by the claims of this application.
Claims
1. A method for preparing an adhesive microneedle patch for tracheal fistula occlusion, characterized in that: The following steps are involved: (A) Preparation of microneedle patch master mold: The master mold was prepared by grayscale photolithography using polydimethylsiloxane; the master mold consisted of 10×10 conical microneedles, with a needle tip spacing of 750μm, a microneedle base diameter of 250μm, a height of 750μm, and a needle tip radius of <15μm; a 1cm×1cm×0.5cm cubic patch mold was set in the middle of the master mold; (B) Preparation of a double-layer microneedle patch based on mussel adhesive protein: Preparation of microneedle tips: Load the first layer of 35 μL of pre-hydrogel solution, including 70% (wt. vol. -1 ) silk fibroin solution, 10 μg of PEGylated manganese-doped hollow mesoporous silica nanoparticles loaded with growth-promoting factors, 1 mM Ru(II)bpy3 2+ and 30 mM sodium persulfate dissolved in PBS; Place into the microneedle patch master mold and dry in a vacuum system (-85 kPa) for 15 minutes; Preparation of microneedle base: Load the second layer of hydrogel pre-solution, including 35% (wt. vol. -1 ) mussel adhesive protein, 15% (wt.vol -1 ) hyaluronic acid, 1mM Ru(II)bpy3 2+ and 30 mM sodium persulfate dissolved in PBS; the second layer of hydrogel at the cubic patch was a 20 μM ROS-responsive polyvinyl alcohol-phenylboronic acid acrylate-quercetin hydrogel compounded in the pre-hydrogel solution and dried under -85 kPa vacuum for 12 hours; the completely dried microneedle patch was then gently peeled off from the mold; throughout the production process, fluorescent illumination was used to ensure that blue light triggered the cross-linking between the tyrosine residues of mussel adhesive protein and silk fibroin.
2. The method for preparing the adhesive microneedle patch for tracheal fistula occlusion according to claim 1, characterized in that: The growth promoting factors described in step B include fibroblast growth factor, insulin-like growth factor, and vascular endothelial growth factor. The concentration of vascular endothelial growth factor and fibroblast growth factor is 10 ng mL -1 , IGF concentration was 20 ng mL -1 .
3. The method for preparing the adhesive microneedle patch for tracheal fistula occlusion according to claim 1, characterized in that: The method for preparing the polyethylene glycol manganese doped hollow mesoporous silica nanoparticles described in step B comprises the following steps: Synthesis of mesoporous silica nanoparticles: Hexadecyltrimethylammonium chloride and triethanolamine were sequentially diluted with water under magnetic stirring at 80°C for 20 min; ethyl silicate was added dropwise to the solution, and the mixture was stirred at 80°C for another 4 h; the product was collected by centrifugation at 18000 r / min for 15 min and washed three times with ethanol and water to remove residual precursors and reactants; the surfactant impurities were removed by stirring in 8 mg / mL sodium chloride methanol solution for 3 rounds; Synthesis of manganese-doped hollow mesoporous silica nanoparticles: The synthesized mesoporous silica nanoparticles were dispersed in water; a mixed solution of 8 mg / mL MnSO4-H2O and 10 mg / mL disodium maleate was added dropwise to the aqueous solution of the mesoporous silica nanoparticles under stirring; the mixture was treated hydrothermally at 180°C for 12 h; the product was collected by centrifugation and washed several times with ethanol and water to remove the residual reactants; PEGylation of manganese-doped hollow mesoporous silica nanoparticles: Manganese-doped hollow mesoporous silica nanoparticles were dispersed into 0.5 mg / mL M-SLN-2000 ethanol solution under magnetic stirring at 60°C; after reacting for 24 hours, the PEGylated manganese-doped hollow mesoporous silica nanoparticles were collected by centrifugation; the product was rinsed with ethanol and deionized water several times to remove residual M-SLN-2000.
4. The method for preparing the adhesive microneedle patch for tracheal fistula occlusion according to claim 1, characterized in that: The preparation method of the ROS-responsive polyvinyl alcohol-phenylboronic acid acrylate-quercetin-loaded hydrogel described in step B comprises the following steps: a) 5 g of polyvinyl alcohol and deionized water (100 ml) were mixed together and stirred at 90° C. to obtain a clear solution; b) quercetin was added to the clear solution, and quercetin was dissolved in DMSO at a concentration of 20 μM; c) 5% mass fraction aqueous solution of phenylboronic acid acrylate and 5% mass fraction aqueous solution of polyvinyl alcohol added with quercetin were mixed in a volume ratio of 1:1, and a hydrogel was immediately formed.
5. An adhesive microneedle patch for tracheal fistula occlusion, characterized in that: The preparation is obtained by the preparation method according to any one of claims 1 to 4.
6. Use of the adhesive microneedle patch as claimed in claim 5 in preparing a product for treating tracheal fistula.
7. The use according to claim 6, characterized in that: The product for treating tracheal fistula is a product used for blocking tracheal fistula.
8. The use according to claim 6, characterized in that: The product for treating tracheal fistula is a product used for repairing tracheal defective tissue.
